2022
DOI: 10.1097/rlu.0000000000004004
|View full text |Cite
|
Sign up to set email alerts
|

Malignant External Otitis in a Patient With Diabetes Mellitus

Abstract: We reported a 66-year-old woman with malignant external otitis who was referred to our department for evaluation of disease extension. Both 99m Tc-MDP bone SPECT/CT and 68 Ga-citrate PET/CT were done for the patient. Both studies showed concordant areas of increased uptake in the petrous bone. In addition, 68 Ga-citrate PET/CT showed soft tissue infection in the nasopharyngeal wall. Our case showed the potential of 68 Ga-citrate PET/CT for evaluation of malignant external otitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…It was the only tracer documented in the literature which dropped in uptake consistently with improvement in the infection 38,40 . 111In works similarly to Ga67 by binding to leucocytes and accumulating in inflammatory tissue making it a useful marker in skull base osteomyelitis 29,41 . There is limited available evidence on its use in the resolution of infection and so further research is required to investigate whether it would be as useful as Ga67 in the follow‐up of NOE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was the only tracer documented in the literature which dropped in uptake consistently with improvement in the infection 38,40 . 111In works similarly to Ga67 by binding to leucocytes and accumulating in inflammatory tissue making it a useful marker in skull base osteomyelitis 29,41 . There is limited available evidence on its use in the resolution of infection and so further research is required to investigate whether it would be as useful as Ga67 in the follow‐up of NOE.…”
Section: Discussionmentioning
confidence: 99%
“…38,40 111In works similarly to Ga67 by binding to leucocytes and accumulating in inflammatory tissue making it a useful marker in skull base osteomyelitis. 29,41 There is limited available evidence on its use in the resolution of infection and so further research is required to investigate whether it would be as useful as Ga67 in the follow-up of NOE. Due to this level of detail, two separate studies found Ga67 radionucleotide scans are more sensitive in the early detection of NOE when compared to CT and MRI.…”
Section: Radionucleotide Scansmentioning
confidence: 99%